Diagnosing Tuberculosis for the First Time at Autopsy - Urooj Husain, Saima Manzoor, Durdana Zafar, Imran Jawaad, Amna Zafar Khan, Shazia Umer (Pakistan Journal of Medical & Health Sciences, 2023)
Among the most common infectious diseases in the developing and underdeveloped countries Tuberculosis stands high and is among one of the leading cause of death in infectious diseases. Government of Pakistan have no doubt supported and started many programs to tackle the problem and have tremendous efforts to eradicate this disease. Stating from diagnosis and providing treatment free of cost of a large group of population. Inspite of all these efforts tuberculosis is still raising due to multiple factors. The rise in the number of patients mainly factors involved are unawareness on the part of the patient and doctor as well. Lacks of education, poor compliance, ignorance, poor follow up are among the main reasons on the part of the patient which lead to a rise in the number of patient annually. Among living patients only 40% are diagnosed. This study is done to determine tuberculosis at autopsy which was diagnosed during life of the patient. Awareness about the disease and its high prevalence in Pakistan is essential to reduce missed diagnoses. Keywords: Diagnosis, Tuberculosis, Forensic Medicine, Autopsy, Evidence